Hydrophilic/Hydrophobic Properties of Silica Surfaces Modified with Metal Oxides and Polydimethylsiloxane - A.G. Dyachenko; M.V. Borysenko; S.V. Pakhovchyshyn (Adsorption Science & Technology)
Microcalorimetry and measurements of the contact angle of water were performed to investigate the hydrophilic/hydrophobic properties of silica surfaces modified with metal oxides and polydimethylsiloxane (PDMS) at 20–500°C. Fumed silicas whose surfaces contained grafted oxygen compounds of metals were used as adsorbents, with VOCl 3 , CrO 2 Cl 2 , TiCl 4 , SnCl 4 , AlCl 3 and Zn(acac) 2 vapours being applied as modifiers. It was found that the hydrophobic coating of silicas modified with metal oxides and PDMS (8–40 wt%) was stable over the temperature range 100–350°C. With a titania coating, the hydrophobic properties were retained at temperatures up to 500°C for an adsorbed polymer content of 20–40 wt%.